2022
DOI: 10.1017/s0272263122000249
|View full text |Cite
|
Sign up to set email alerts
|

The elusive impact of L2 immersion on translation priming

Abstract: A growing consensus sees the bilingual lexicon as an integrated, nonselective system. However, the way bilingual experience shapes the architecture and functioning of the lexicon is not well understood. This study investigates bilingual lexical-semantic representation and processing employing written translation priming. We focus on the role of active exposure to and use of the second language (L2)—primarily operationalized as immersion. We tested 200 highly proficient Spanish–English bilinguals in two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…However, the effect of language direction was not significant, meaning that the effects in both directions were of similar strength. This is unexpected, since previous studies have generally found a smaller translation priming effect in the L2-L1 direction (Chaouch-Orozco et al, 2022;review in Wen & van Heuven, 2017), even in balanced bilinguals (Basnight-Brown & Altarriba, 2007;see Duñabeitia et al, 2010, for different results).…”
Section: Discussionmentioning
confidence: 76%
“…However, the effect of language direction was not significant, meaning that the effects in both directions were of similar strength. This is unexpected, since previous studies have generally found a smaller translation priming effect in the L2-L1 direction (Chaouch-Orozco et al, 2022;review in Wen & van Heuven, 2017), even in balanced bilinguals (Basnight-Brown & Altarriba, 2007;see Duñabeitia et al, 2010, for different results).…”
Section: Discussionmentioning
confidence: 76%
“…Participants 200 highly proficient, late sequential Spanish-English bilinguals (164 females, 36 males) were tested in two lexical decision experiments, one for each translation direction (see Table 1 for participants characteristics). The main focus in Chaouch-Orozco et al (2022) was to investigate how immersion in the second language affected priming effects. To this purpose, participants were divided into two equally large groups manipulating this factor (i.e., immersed vs nonimmersed).…”
Section: Methodsmentioning
confidence: 99%
“…The present study aims to make a significant contribution in this regard. We re-analysed a translation priming dataset from Chaouch-Orozco et al (2022). Their study followed up on a previous investigation on the role of language experience on translation priming effects (Chaouch-Orozco et al, 2021), with a more comprehensive scope.…”
Section: The Study Of Translation Equivalence Through Concreteness Ef...mentioning
confidence: 99%
See 2 more Smart Citations